Slip-line field modelling of rounded-edge cutting tool for orthogonal machining - Uysal, Alper; Altan, Erhan (SAGE PUBLICATIONS LTD, 2016)
A new slip-line field model and its associated hodograph of rounded-edge cutting tool were developed for orthogonal micro-cutting operation using matrix technique. The new model considers the existence of dead metal zone in front of the rounded-edge cutting tool. The ploughing forces, chip up-curl radii, chip thicknesses, primary shear zone thicknesses and lengths of bottom side of the dead metal zone are obtained by solving the model depending on the experimental resultant force data. The effects of cutting edge radius, uncut chip thickness, cutting speed and rake angle on these outputs are specified.
Keywords: Slip-line field model; rounded-edge cutting tool; dead metal zone; ploughing force; micro-machining; SECONDARY RAKE FACE; ADHESION FRICTION; CHIP CONTACT; PART II; ROUNDNESS; INTERFACE; STRAIN; Engineering